Reliability of Beta-Human Chorionic Gonadotropin in Ectopic Pregnancy - SATHYA SELVARAJAN (Journal of Clinical and Diagnostic Research, 2018)
Introduction: A fertilized ovum implanting external to the uterine cavity is an Ectopic Pregnancy (EP). It is one of the leading causes of first trimester maternal morbidity and mortality around the globe. Aim: To assess the clinical manifestation, predisposing factors, beta-hCG values and mode of treatment associated with EP in a tertiary care hospital. Materials and Methods: Analysis of patients, admitted with EP to Sri Ramachandra Medical College Hospital for one year, was done. All the data was collected from the case records of 116 patients. Charts were reviewed to determine patient symptoms, gestational age, ultrasound findings, beta-hCG assay values and mode of treatment. Results: Maximum (49.2%) cases belonged to the age group of 26 to 30 years and most of cases (40%) were multiparous. Major risk factor was the usage of assisted reproductive technologies besides having previous bad obstetric histories. Most patients presented with complaints of bleeding per vaginum and/or pain abdomen. Majority of women presented at the 7th week of gestation. There was a weak correlation (0.392) between the weeks of gestation and the beta-hCG values. Major modality of treatment was surgery (56.3%) while the remaining patients were managed medically or conservatively. No mortality was encountered in this series. Conclusion: Women with risk factors like assisted reproductive technologies and bad obstetric history should be screened for EP in their subsequent pregnancies. There is an overlap of values of beta-hCG obtained in EP with normal pregnancy, especially during the 4th and 5th weeks of gestation. Further studies with an increased sample size, from 6th week of gestation onwards, will throw light on this issue.